3D microwave vibrometer: Contactless three-dimensional vibration measurements using microwave radars. (15th January 2023) - Ren, Zesheng; Xiong, Yuyong; Peng, Zhike; Meng, Guang
Highlights: An innovative three-dimensional vibration measurement method using microwave radars is proposed. Accurately reconstruct three-dimensional vibration trajectory of target and measure its displacement at three orthogonal axes using three single microwave radars' vibration measurement results. Theorical error analysis is done to give out the factors and their upper bounds that influence the 3D vibration measurement results. Simulation and experimental validations with different scenarios are presented to demonstrate the performance of our proposed 3D microwave vibrometer. Abstract: The emerging radar-based vibration measurement technology has attracted much interest in a wide spectrum of applications, such as mechanical test, structural health monitoring, machine diagnosis and vital sign detection. Advances in large monitoring range, high accuracy and excellent test efficiency and environmental adaptability have allowed radar-based vibration measurement method to perform enough superiority over traditional contact measurements like accelerometers or optical ways such as laser triangulation sensors or video/image-based measurements. However, the state of the art for radar vibration measurements mostly focuses on the quantification of one-dimensional vibrational measurement. This paper aims to present an accurate three-dimensional (3D) vibration measurement approach using three microwave radars via linear frequency modulated continuous wave (LFMCW) radars. The system overview and fundamental concept are illustrated firstly. To achieve 3D space trajectory and displacement of a vibrating target, we show the detailed procedures about coordinate system establishment and 3D displacement reconstruction process. Moreover, the error factors and analysis involved in our method are also discussed, allowing robust and accurate measurement for practical applications. Simulation and experimental validations are provided for demonstrating the performance of the method, offering a desired approach for contactless 3D vibration and displacement measurement.